Evaluation of Mammalian Interspersed Repeats to investigate the goat genome - P. Mariani; F. Panzitta; A. Stella; C. Gorni (Italian Journal of Animal Science, 2010)
Among the repeated sequences present in most eukaryotic genomes, SINEs (Short Interspersed Nuclear Elements) are widely used to investigate evolution in the mammalian order (Buchanan et al., 1999). One family of these repetitive sequences, the MIR (Mammalian Interspersed Repeats; Jurka et al., 1995), is ubiquitous in all mammals.MIR elements are tRNA-derived SINEs and are identifiable by a conserved core region of about 70 nucleotides.